A STUDY ON MICRO IRRIGATION TECHNOLOGY ADOPTION WITH SPECIAL REFERENCE TO DINDIGUL - A. Archana; V. Suthacini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In India, micro irrigation technology was introduced in the 1970‘s to overcome the severe depletion of ground water in many areas of India due to overexploitation of ground water in irrigating crops. Tamil Nadu is one of the key implementing states for the micro irrigation system in India. Nowadays, micro irrigation is known as the most precise, efficient, and practical method of delivering water and nutrients to crops. The adoption of micro-irrigation technologies (MIT) has emerged as a critical solution for enhancing water use efficiency in agriculture, particularly in water-scarce regions. This study focuses on the adoption patterns of micro irrigation systems in Dindigul District, Tamil Nadu. This study based on secondary data obtained from various government reports, agricultural surveys, and research publications. Dindigul, a predominantly agricultural district, faces challenges related to water scarcity and erratic rainfall, making it an ideal location to analyze the impact and diffusion of MIT.The research aims to assess the extent of adoption of micro irrigation practices such as drip irrigation and sprinkler systems.